PENERAPAN METODE EKSPERIMEN PADA SISWA KELAS V - Endah Padmawati (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2021)
The purpose of this classroom action research is to improve the science learning outcomes of elementary school students. Meanwhile, it plans to improve scientific learning outcomes for fifth-grade students at SD Negeri Medani 02. Sixteen fifth-grade students from SD Negeri Medani 02, six males and eight females, took part in this study. The test method was used to collect data for this study. The subject matter was covered in the test, which included magnetic forces, gravitational forces, friction forces, and simple planes. The findings revealed that using a variety of experimental methodologies could improve the scientific learning outcomes of fifth grade students at SD Negeri Medani 02 From an initial condition of 59.00 to a final condition of 74.375. According to the submission of hypotheses based on theoretical studies, the experimental method can improve learning outcomes of Science in Energy and its Changes for fifth grade students of SD Negeri Medani 02 Cluwak Pati, namely the experimental method can improve learning outcomes of Energy Science and its Changes for fifth grade students of SD Negeri Medani 02 Cluwak Pati.Keywords: learning outcomes, experiment